THE PROMOTION STRATEGY AND THE PROBLEMS OF ORGANIZING WIRA USAHA BARU (WUB) PROGRAM BY BANDUNG GOVERNMENT: COOPERATIVE, MICRO, SMALL, AND MEDIUM ENTERPRISES AGENCY AND EDUCATION AGENCY - Abdalla, Ikhsan
The Indonesian President, Joko Widodo, in 2018 stated that the number of Indonesian entrepreneurs was still at 3.1%. He also said that the average ratio of the number of entrepreneurs in the developed countries was 14%. This figure is also still behind compared to neighboring countries such as Singapore 7%, Malaysia 5%, and Thailand 4.5%. Therefore a government program is needed to accelerate the increase in the number of entrepreneurs. Ridwan Kamil, Mayor of Bandung for the 2013-2018 period had a campaign promise to create 100,000 new entrepreneurs in the city of Bandung under the name of the New Business Entrepreneurship Program, Wira Usaha Baru (WUB). The WUB program is divided into five Bandung City Government Agencies to be implemented. The researcher conducted research to the Agency of Cooperatives and Micro, Small, Medium Enterprises (MSMEs) and the Bandung City Education Agency where these two agencies had the largest number of targets. Each of the two agencies received 35,000 and 53,000 WUB target planned. Researchers get data that the target given cannot be reached, not even up to 20%. The Agency of Cooperatives and Micro, Small, and Medium Enterprises (MSMEs) can only reach 4,134 WUB and 8,775 for Education Agency. Based on this, researcher are interested in identifying problems that are faced so that the target of the WUB program cannot be achieved. The researcher also wants to identify how the WUB program promotion strategy to the community. The theory that is used as a reference for researchers are the Integrated Marketing Communication (IMC) and AIDA Model. The IMC theory will be used to analyze information provided by the agency about the promotional strategies used. The AIDA theory is aimed at WUB participants to clarify information provided by the agency. The study was conducted using qualitative methods with in-depth interviewing techniques because the data needed must be obtained directly through key informants from the agency office and data clarification to WUB participants. The researcher grouped the types of questions into three parts aspects of the WUB program promotion strategy, WUB program implementation, and WUB program problems. After collecting data and analyzing data, the researchers got the results there is the difference in the program promotion strategy and implementation of the WUB program between the Cooperative, MSMEs and Education Agency, but the problems faced were almost the same. The promotion strategy of the WUB program is carried out by the Agency of Cooperatives, MSMEs by placing advertisements and brochures in the Kecamantan/ Kelurahan Offices, regional radio, regional television, and spreading information by word of mouth through the WhatsApp group. While the Education Agency handed over the process of program promotion to third parties namely LKP (Institute for Skills and Training). The implementation of the WUB program carried out by the Agency of Cooperatives, MSMEs in the form of providing theories about marketing, finance, legality, business motivation, and skills training. While the Education Agency handed over all WUB activities from promotion, recruitment, and implementation to the LKP and the LKP only give the skills training without business theories as Cooperatives, MSMEs Agency did. The problems faced are almost the same a large number of targets given by the mayor, budget constraints, limited time, limited human resources, lack of coordination between program administrators, and specifically for the Agency of Education limited LKP capacity. The results of the study show the number of problems faced during implementing the WUB program and not optimal promotion strategy of the WUB program carried out by the agencies. The researcher recommended several solutions for the next government program. First in the era of advances in information and communication technology now, the government needs to create software that can integrate between agencies and other government institutions so that coordination can be done easily. Then for mayors candidates, they should first conduct research on the ability of the Regional Budget (APBD) and the ability of the agency to implement a program. Next, the agency can optimize the promotion stratgegy with put the advertising in online media because it can reach the public in large numbers. Agency can work together with online advertising services company in Bandung such as @InfoBDG and others. In addition agency can use direct marketing strategbesides cooperating with Kecamatan/ Kelurahan Offices, the agency can also work with RT / RW parties that are closer to the community to be able to provide information directly to the community. This research hope can impact to maximize government action in implementing a program.